Enforcement of Criminal Sanctions Against Trafficking of Protected Wildlife in Sorong City - Ikhsan, Muhibbul; Hidaya, Wahab Aznul; Muharuddin, Muharuddin (Journal of Law Justice (JLJ), 2025)
This research aims to find out the Enforcement of Criminal Sanctions Against Protected Wildlife Trade in Sorong City To find out the obstacles in the application of Enforcement of Criminal Sanctions Against Protected Wildlife Trade in Sorong City. This type of research is normative juridical research, data sources in this research are primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data obtained by library techniques and analyzed descriptively quantitative. The results showed that (1) Positive law in Indonesia distinguishes between “wildlife” and “pets” to protect biodiversity. Based on the Regulation of the Minister of Environment and Forestry Number P.20/MENLHK/SETJEN/KUM.1/6/2018, there are 794 species of animals and 130 species of plants that are protected. Exploitation of protected wildlife is considered a criminal offense, as stated in Article 302 paragraph (1) of the Criminal Code which stipulates penalties for animal protection offenses. (2) Based on interviews with police officers in Sorong, it is known that there are law enforcement efforts against the trade of endangered animals, which involves cooperation between the Sorong Police and the Natural Resources Conservation Center (BKSDA) to ensure animal protection. This effort reflects an active role in implementing animal protection and raising awareness of animal welfare, which is part of moral norms. The effectiveness of law enforcement is also influenced by the structure, substance, and culture of law, in accordance with Lawrence Friedman's theory, as well as the five factors of legal effectiveness according to Soerjono Soekanto. This research shows that strengthening the substance of the law through criminal sanctions can provide a deterrent effect and prevent rare animal trade crimes, but structural and cultural improvements are still needed to achieve optimal success.